Problematika Implementasi Kurikulum Merdeka di SMP Angkasa Padang - Nur Fadilah Putri; Keysha Ardian Fatika; Habib Rizki; Merika Setiawati; Luthfiani Luthfiani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research was conducted with the aim of Finding and describing the problems faced in implementing the independent curriculum at the Angkasa Padang Primary School. This research is motivated by the many problems related to the implementation of the independent education curriculum and various policies related to the independent education curriculum. The research question asked is: What problems exist in implementing the unique curriculum at Angkasa Padang Middle School? This research was conducted as quantitative research. Data collection was carried out through a questionnaire survey at Angkasa Padang School. These observations are analyzed and presented in a descriptive format. The results of this analysis can answer the questions formulated in the research problem. The results of the analysis reveal problems in implementing the voluntary curriculum which are caused by less than optimal government guidance and support in implementing the voluntary curriculum. Apart from that, there are challenges originating from teachers in the form of using independent teaching platforms and their lack of ability to utilize technology to learn and understand the independent curriculum.